A postcolonial approach to Trauma in Toni Morrison’s gothic novel Home (2012) - Djekidel ,Halima Saadia; Sebgagui ,Noura; Selt, Djihad Afaf (Faculty of Letters and Foreign Languages Department of English, 2023)
African American history has gone through important phases characterized by cruel events, including property dispossession, police brutality, and many other brutal acts that haunted the past and traumatized the present of black people. This study is an attempt to analyse the novel Home and cover the main events that happened in the course of 1950s in the United States, especially during the Korean War, by presenting the psycho-traumatic dimension, white medical experimentation, and trauma war in the novel since it reveals numerous realistic facts about a neglected historical period and describes how African Americans suffered from. This dissertation tries to investigate the representation of the struggle of African Americans in Toni Morrison‟s Home and reveal the traumatizing experience they underwent. It also aims to show how Morrison‟s narrative tends invert the dominant western assumptions. This dissertation is carried out using a postcolonial along with psychoanalytical approaches. It follows a descriptive method in order to scrutinize blacks sufferings within a postcolonial context, drawing on history, memory, gothic fiction. Finally, this study concludes that the traumatizing impacts in Toni Morrison‟s Home have both psychological and physical negative effects